**Covid-19 has led the world to go through a phenomenal transition .**

**E-learning is the future today.**

**Stay Home , Stay Safe and keep learning!!!**

A function can be implicit or explicit.

Explicit formWhen 'y' is expressed as function of x then such a function is called Explicit function.For example : 1) y = $x^{2}$ +1 2) y = sin(x) + $x^{3}$ 3) y = $\sqrt{x+1}$ |
Implicit formWhen the function is expressed in terms of x and y then such equations are called Implicit form.For example : 1) $x^{2} + y^{2}$= 5 2) $x^{2}$ + xy = 0 3) $y^{3} -y^{2} + x^{2}$= 0 |

Implicit differentiation : So far we have discussed derivatives of the function y = f(x). If the derivatives x and y are connected by a relation of the form f(x,y)= 0 and sometimes it is not possible to express y as a function of x in the form of y = g(x) then y is said to an implicit function of x. To find dy/dx in such a case, we differentiate both sides of the given relation with respect to x. So to differentiate such functions we use a chain rule.

Differentiating both sides with respect to x, we get

$\frac{d}{dx}(x^{2})+ 2 \frac{d}{dx}(xy) + \frac{d}{dx}(y^{3}) = \frac{d}{dx}(42)$

Apply the power rule, product rule and chain rule for differentiation

2x + 2(x.$\frac{dy}{dx} + y.1) + 3y^{2}\frac{dy}{dx}$ = 0

2x + 2x. $\frac{dy}{dx} + 2y + 3y^{2}\frac{dy}{dx}$ = 0

2x + 2y + $\frac{dy}{dx}(2x + 3y^{2})$ = 0

$\frac{dy}{dx}(2x + 3y^{2})$ = -2x - 2y

$\frac{dy}{dx}(2x + 3y^{2})$ = -(2x + 2y)

$\frac{dy}{dx} = \frac{-(2x + 2y)}{(2x + 3y^{2})}$

**Example 2 : ** If sin(y) = x.sin(a + y) , find $\frac{dy}{dx}$

**Solution : ** We have sin(y) = x.sin(a + y)

Differentiating both sides with respect to x, we get

$\frac{d}{dx}(sin(y))= \frac{d}{dx}[x.sin(a + y)] $

Apply the product rule and chain rule for differentiation

cos(y)$\frac{dy}{dx}= 1.sin(a + y) + x.cos(a+ y) \frac{d}{dx}(a + y)$

cos(y)$\frac{dy}{dx}= sin(a + y) + x.cos(a+ y)[ \frac{d}{dx}(a) + \frac{dy}{dx}] $

cos(y)$\frac{dy}{dx}= sin(a + y) + x.cos(a+ y) . \frac{dy}{dx} $

cos(y)$\frac{dy}{dx} - x.cos(a+ y) . \frac{dy}{dx} $ = sin(a + y)

$\frac{dy}{dx}[cos(y) - x.cos(a + y)]$ = sin(a + y)

$\frac{dy}{dx} = \frac{sin(a + y)}{[cos(y) - x.cos(a + y)]}$

Home

**Covid-19 has affected physical interactions between people.**

**Don't let it affect your learning.**

GMAT

GRE

1st Grade

2nd Grade

3rd Grade

4th Grade

5th Grade

6th Grade

7th grade math

8th grade math

9th grade math

10th grade math

11th grade math

12th grade math

Precalculus

Worksheets

Chapter wise Test

MCQ's

Math Dictionary

Graph Dictionary

Multiplicative tables

Math Teasers

NTSE

Chinese Numbers

CBSE Sample Papers